Development Of Professional Competence Of Future Teachers Of Technology In The Process Of Extracurricular Activities - Haydarov Ramozon Mamayusupovich (Academia One Publishing, 2024)
This article focuses on developing the future technology teacher's professional competence in the process of extracurricular activities, raising a spiritually morally mature, independent worldview, a creative thinker, a rich national heritage, as well as a harmonious personality devoted to Universal and national values
Keywords: Information and educational environment; technology; professional competence